2001
DOI: 10.3189/172756501781832403
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy-driven lacustrine calving, Glaciar Nef, Chilean Patagonia

Abstract: Glaciar Nef, a 164 km2 eastern outlet of Hielo Patagónico Norte (the northern Patagonia icefield), terminates in a proglacial lake that has formed in conjunction with 20th-century glacier retreat. The terminus is inferred to be transiently afloat. A hinge-calving mechanism is proposed in which buoyant forces impose a torque on the glacier tongue, resulting in the release of coherent sections of the glacier tongue as “tabular” icebergs. A simple model shows how torque and tensile stress reach a maximum at the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 76 publications
5
69
0
Order By: Relevance
“…While the ice-front position and the flow speed are relatively easy to measure using satellite data, calving and melting in water are difficult to observe. An approach commonly taken in previous studies is to define frontal ablation rate,ȧ, as the sum ofċ andṁ, and compute the frontal ablation as a residual of dL/dt and u m (e.g., Warren et al, 2001;Haresign and Warren, 2005;Luckman et al, 2015;McNabb et al, 2015). Recent studies on tidewater glaciers have shown that calving (ċ) and melting under waterline (ṁ) vary in time under the influence of atmospheric and fjord water conditions (e.g., Benn et al, 2007;Bartholomaus et al, 2013;Luckman et al, 2015;Pȩtlicki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While the ice-front position and the flow speed are relatively easy to measure using satellite data, calving and melting in water are difficult to observe. An approach commonly taken in previous studies is to define frontal ablation rate,ȧ, as the sum ofċ andṁ, and compute the frontal ablation as a residual of dL/dt and u m (e.g., Warren et al, 2001;Haresign and Warren, 2005;Luckman et al, 2015;McNabb et al, 2015). Recent studies on tidewater glaciers have shown that calving (ċ) and melting under waterline (ṁ) vary in time under the influence of atmospheric and fjord water conditions (e.g., Benn et al, 2007;Bartholomaus et al, 2013;Luckman et al, 2015;Pȩtlicki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For buoyant glacier tongues, the ice may be out of hydrostatic equilibrium at the grounding line, resulting in upward-di- rected torque forces (Warren et al, 2001;Boyce et al, 2007;Murray et al, 2015). Reduction in the ice surface elevation or advance of the terminus into deeper water can result in an increase of "superbuoyancy," which may trigger fracture propagation and calving (Benn et al, 2007b;Nick et al, 2009).…”
Section: Mechanically Driven Calvingmentioning
confidence: 99%
“…Several processes can drive the terminus out of buoyant equilibrium, including rapid thinning due to surface melt (Warren et al, 2001), rapid water-level rise (Boyce et al, 2007), enhanced ice flow forcing the terminus to advance into deeper water, and dynamic thinning (Murray et al, 2015). The first two processes can be ruled out for Rink Isbrae as they apply to warm environments with high surface melt rates, and lacustrine systems where small short-term perturbations in lake level lead to rapid increases in water depth.…”
Section: Mechanically Driven Calvingmentioning
confidence: 99%
“…First because such glaciers differ from tidewater glaciers because of lower velocities and calving speed. Second because they can sustain floating tongues for long periods prior to the onset of calving phases (Warren et al, 2001;Boyce et al, 2007). In this study, we propose to apply a flotation model to explain the retreat of the Triftgletscher terminus.…”
Section: Calving Rate Definition and Flotation Levelmentioning
confidence: 99%